Antineoplastic Drug‐Free Anticancer Strategy Enabled by Host‐Defense‐Peptides‐Mimicking Synthetic Polypeptides. Issue 36 (23rd July 2020) - Shen, Wei; Zhang, Yu; Wan, Pengqi; An, Lin; Zhang, Peng; Xiao, Chunsheng; Chen, Xuesi
Abstract: An antineoplastic drug‐free anticancer strategy enabled by host defense peptides (HDPs)‐mimicking synthetic polypeptides is reported. The polypeptide exhibits a broad spectrum of anticancer activity in 12 cancer cell lines, including drug‐resistant and highly metastatic tumor cells. Detailed mechanistic studies reveal that the cationic anticancer polypeptide (ACPP) can directly induce rapid necrosis of cancer cells within minutes through a membrane‐lytic mechanism. Moreover, a pH‐sensitive zwitterionic derivative of ACPP (DA‐ACPP) is prepared for in vivo application. DA‐ACPP shows negligible hemolysis under neutral physiological conditions, and can be converted back to ACPP in slightly acidic tumor environments, resulting in selective killing of cancer cells. Consequently, DA‐ACPP shows an effective inhibition of tumor growth in both 4T1 orthotopic breast tumor models and B16‐F10 melanoma pulmonary metastatic models. Overall, these findings demonstrate that synthetic HDPs‐mimicking polypeptides represent safe and effective antineoplastic agents, which sheds new light on the development of drug‐free synthetic polymers for cancer therapy. Abstract : An antineoplastic drug‐free anticancer strategy enabled by host defense peptides (HDPs)‐mimicking synthetic polypeptides is proposed. The synthetic anticancer polypeptides (ACPP) exhibit broad‐spectrum anticancer activity through an HDPs‐like membrane‐lytic mechanism. Modification of ACPP with 2, 3‐dimethylmaleic anhydride (DA) generates a pH‐sensitive zwitterionic derivative, DA‐ACPP, with improved biocompatibility, which can selectively lyse tumors in vivo after being activated in acidic tumor microenvironment.